EFEKTIVITAS MULTIMEDIA BREASTFEEDING EDUCATION AND REFLECTION PROGRAM (MEDIBERPRO) PADA IBU PRIMIPARA - Siti Maria Ladia Paradisa Syitra; Asniar Asniar; Suryane Sulistiana Susanti (NURSE: Journal of Nursing and Health Science, 2025)
Background: Exclusive breastfeeding (EBF) is the main source of nutrition for babies aged 0-6 months. Several factors related to exclusive breastfeeding are breastfeeding self-efficacy (BSE), attitude, and knowledge of EBF. One recommended method to improve these efforts is to provide multimedia-based education. This study aims to determine the effectiveness of the Multimedia Breastfeeding Education and Reflection Program (MediBERpro) in increasing BSE, knowledge, and attitudes about breastfeeding among primiparous mothers. Method: This research used a quasi-experimental design with pre- and post-tests in the control and intervention groups. The data was collected by an online form involving 93 respondents of primiparous mothers obtained by the snowball technique, and were randomly assigned as the control group (n = 51) or the intervention group (n = 42). Results: The results in the intervention group demonstrated a difference with the control group, where the P value <0.05 [BSE (0.000), knowledge (0.000), attitude (0.000)]. The intervention group between the pre-test and post-test scores demonstrated a significant difference with P value <0.05 [BSE (0.000), knowledge (0.000), and attitude (0.000)]. Conclusion: The conclusion is that MediBERpro can significantly increase BSE, knowledge, and attitudes among primiparous mothers. Therefore, MediBERpro is applicable to increase the EBF rate. 000) and attitude (0.000)). The conclusion is that MediBERpro can significantly increase BSE, knowledge, and attitudes among primiparous mothers. Therefore, MediBERpro is applicable to increase the rate of EBF. 000) and attitude (0.000).   Keywords: Academic burnout, nursing students, peer assessment, self-efficacy